Epidemiology of burn-related fatalities in Australia and New Zealand, 2009–2015. Issue 7 (November 2019) - McInnes, Judith A.; Cleland, Heather J.; Cameron, Peter A.; Darton, Anne; Tracy, Lincoln M.; Wood, Fiona M.; Singer, Yvonne; Gabbe, Belinda J.
Highlights: From 2009 to 2015, 310 burn-related fatalities occurred in Australia and New Zealand. 41% of these fatalities occurred in a pre-hospital setting. One quarter of all fatalities were a consequence of self-inflicted harm. A majority of fatalities were male, and were aged 41–80 years. The population incidence of fatalities in NSW decreased over the study period. Abstract: Background: Knowledge of the epidemiology of burn-related fatalities is limited, with most previous studies based on hospital and burn centre data only. Aims: To describe the epidemiological characteristics of all burn-related fatalities in Australia and New Zealand, and to identify any trends in burn-related fatality incidence over the study period. Methods: Data from the National Coronial Information System, including data for pre-hospital and in-hospital burn-related fatality cases, was used to examine the characteristics of burn-related fatalities occurring in Australia and New Zealand from 2009 to 2015. Burn-related fatality rates per 100, 000 population were estimated, and incidence trends assessed using Poisson regression analysis. Results: Of the 310 burn-related fatalities that occurred in Australia and New Zealand, 2009–2015, 41% occurred in a pre-hospital setting. Overall, most burn-related fatality cases were fire related, occurred at home, and were of people aged 41–80 years. One quarter of all burn-related fatalities were a result of intentional self-harm. The population incidence of all burn-related fatalities combined, and for NSW, decreased over the study period. Conclusions: This study has identified the importance of examining all burn-related fatalities. If this is not done, vulnerable population subgroups will be missed and prevention efforts poorly targeted.